2016
DOI: 10.4103/0976-7800.191013
|View full text |Cite
|
Sign up to set email alerts
|

Preventable risk factors for osteoporosis in postmenopausal women: Systematic review and meta-analysis

Abstract: Background and Objective:The osteoporosis is becoming public health problem in India and neighboring Asian countries. As the environmental risk factors for osteoporosis in women are similar in these countries, the study was planned to compare risk factors for osteoporosis in postmenopausal women in Asian countries.Materials and Methods:A systematic literature search was done in August 2015. The period included for this search was from January 2005 to December 2014. The search was done for India and neighboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 21 publications
1
23
1
1
Order By: Relevance
“…As expected, the group of postmenopausal women diagnosed with osteoporosis had a significantly higher mean age than the osteopenic or unaltered group, corroborating with results presented by other studies, since the advance in age is inversely associated with BMD (26)(27)(28) . Regarding the anthropometric variables that characterize the sample, it was observed that women with no alteration in BMD presented significantly greater height than osteoporotic women, however, with no differences for body weight or BMI.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As expected, the group of postmenopausal women diagnosed with osteoporosis had a significantly higher mean age than the osteopenic or unaltered group, corroborating with results presented by other studies, since the advance in age is inversely associated with BMD (26)(27)(28) . Regarding the anthropometric variables that characterize the sample, it was observed that women with no alteration in BMD presented significantly greater height than osteoporotic women, however, with no differences for body weight or BMI.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the anthropometric variables that characterize the sample, it was observed that women with no alteration in BMD presented significantly greater height than osteoporotic women, however, with no differences for body weight or BMI. A recent systematic review and meta-analysis involving postmenopausal women confirmed that among these three variables, height is the one that is most strongly associated with the diagnosis of osteoporosis, with no evidence for body weight or BMI, which limits interventions as this variable is not modifiable (26) . Contrary to our initial hypothesis, the isokinetic peak torque of knee extensors and flexors at 60º/s and 180º/s was not significantly different between BMD classifications, nor was there any significant correlation between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…O steoporosis is a severe condition of low bone mineral density (BMD). Patients with osteoporosis have a high fracture hazard, leading to physical impairment, significant pain and even untimely death (Lloret et al, 2016;Thulkar et al, 2016;Weisz, 2017). Preventive treatments include maintaining or increasing bone mineral density (BMD) when its loss is induced by decreasing levels of sex steroid levels with age in both males and females (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“… 4 However, the rate of osteoporosis is far higher in Asian population, and it has been estimated that about 50% of the people will be victims of osteoporosis by 2050. 10 Furthermore, this problem is more centered in populations residing in the rural areas, and a majority of population in Nepal live in such communities where people with osteoporosis remain undiagnosed. Specially in our country, 50% of the total population are women, and among them greater than 50% are elderly, 11 and this is the group that is at high risk for osteoporosis.…”
Section: Introductionmentioning
confidence: 99%